2019
DOI: 10.1177/2325958219888457
|View full text |Cite
|
Sign up to set email alerts
|

Moderately High Tenofovir Diphosphate in Dried Blood Spots Indicates Drug Resistance in Viremic Persons Living with HIV

Abstract: Background: Tenofovir diphosphate (TFV-DP) in dried blood spots (DBS) is a strong predictor of viral suppression in persons living with HIV (PLWH). Its association with antiretroviral therapy (ART) resistance remains unknown. Methods: Blood was collected in PLWH receiving TDF-containing ART enrolled in a 48-week study. Tenofovir diphosphate/emtricitabine triphosphate (FTC-TP) were quantified from the same sample as HIV viral load (VL) in PLWH who developed resistance within ≤12 months. Results: The study enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…Although the concentrations of TFV-DP in virologically suppressed PWH in our study were lower than previously observed in the United States [21], they are consistent with other studies in Africa [22,29,30]. Our findings are also consistent with a clinical cohort of PWH in the United States, where TFV-DP concentrations in study participants who developed new drug resistance-associated mutations were ∼40% lower than those observed in participants who were virologically suppressed [21,24]. These results are also similar to other studies that assessed ART adherence using qualitative [31,32] and other cumulative [15,33] pharmacologic measures.…”
Section: R E S U Lt S a N D Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although the concentrations of TFV-DP in virologically suppressed PWH in our study were lower than previously observed in the United States [21], they are consistent with other studies in Africa [22,29,30]. Our findings are also consistent with a clinical cohort of PWH in the United States, where TFV-DP concentrations in study participants who developed new drug resistance-associated mutations were ∼40% lower than those observed in participants who were virologically suppressed [21,24]. These results are also similar to other studies that assessed ART adherence using qualitative [31,32] and other cumulative [15,33] pharmacologic measures.…”
Section: R E S U Lt S a N D Discussionsupporting
confidence: 92%
“…However, its ability to identify treatment failure (i.e. VF) with drug resistance is poorly understood [24].…”
Section: Introductionmentioning
confidence: 99%
“…This group was also more diverse and contained both individuals who had maintained viral suppression and those who had not. This demonstrates that relying on viral load alone to assess adherence could be inadequate as it has been previously shown that mid-range adherence is more strongly associated with the development of ART resistance [25]. It has also been shown that TFV-DP in DBS, in combination with viral load, can be used to identify PWH with suspected ART resistance [22,25].…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 17 More informative, however, would be high viremia in patients with high cumulative adherence, which is most likely due to antiretroviral resistance. 18 – 20 Thus, when facing this clinical presentation (i.e., high adherence and high viremia), providers could be more inclined to order HIV drug resistance testing rather than have repeated discussions about adherence (with the potential of further perpetuating the accumulation of drug resistance).…”
Section: Viremia With High Drug Concentrationsmentioning
confidence: 99%